2019
DOI: 10.1504/ijmdm.2019.100493
|View full text |Cite
|
Sign up to set email alerts
|

An integrated core competence evaluation framework for portfolio management in the oil industry

Abstract: is an experienced academic with over 25 years of teaching, research, educational management and technology transfer experience across disciplines in the UK and TNE. Before his most recent appointment as Professor and Head of Business & Management Division at the Dundee Business at Abertay Dundee, he served as the Professor at the Claude Littner Business School at the University of West London and professor and head of group at the York Management School, University of York UK. Prior to this he was Reader and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…This relationship indicates that people-based practices (P) are the most prominent core competencies of manufacturing and service organizations in Pakistan compared to technology (T) and organization (O) factors. The outcomes of people factors support studies done in the past, and those empirically suggested similar results (Hafeez & Essmail, 2007;Hafeez & AbdelMeguid, 2003). In the KBV, the findings of H3 are constant with Tan & Wong (2015) for KM factors to significantly enhance manufacturing performance and Andreeva & Kianto (2012) as they observed a strong influence of technology and people practices on firm competitiveness.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…This relationship indicates that people-based practices (P) are the most prominent core competencies of manufacturing and service organizations in Pakistan compared to technology (T) and organization (O) factors. The outcomes of people factors support studies done in the past, and those empirically suggested similar results (Hafeez & Essmail, 2007;Hafeez & AbdelMeguid, 2003). In the KBV, the findings of H3 are constant with Tan & Wong (2015) for KM factors to significantly enhance manufacturing performance and Andreeva & Kianto (2012) as they observed a strong influence of technology and people practices on firm competitiveness.…”
Section: Discussionsupporting
confidence: 86%
“…The finding suggests that the more manufacturing and service firms develop core competence, the more firm increases their competitiveness and lead performance of their unique and distinctive products and services. Previously, technology (T) and organization (O) factors remained a significant core competence of competitive advantages in many previous studies from different countries (Hafeez et al, 2010;Hafeez & Essmail, 2007). While in Pakistan, this result indicates that T and O are less contributing factors to competitiveness in larger sectors of Pakistan.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations